Investigation of particle penetration through building cracks - Yu, Zhou Hang. (2011)
Contaminants may be carried by air particles from outdoors to indoors through cracks in the building envelop. This project aimed to experimentally investigate the efficiency of airborne particles can penetrate through those building cracks. Two chambers were made and linked a slot that mimics a building crack. A small pressure difference was established between the two chambers, which induce the air flow through the slot. Indoor refers to home and factory building and outdoor refers to the environment surrounding the former two. The crack size for the experiment can be adjusted by adding the number of slots and pressure difference of the two chambers could be varied. Experiment data was collected base on the particle concentration, pressure difference of the two chambers and the crack size. Slot has a triangular cross sectional area, its height is 4 mm, width is 3 mm and length is 50mm and 150mm. increase number of slots or the length of the slots, the penetration result will be affacted. Particle penetration diminishes for larger particles as well as small pressure difference. Particle penetration increases when the number of slots increase (the flow cross sectional area increase) for all particle sizes.